Investigating the Cultural and Social Effects of Football among the Students of Physical Education Department at Kandahar University - Enayatullah Dadman; Sultan Mohammad Stanikzai; Khalid Amarkhil (Universitas Majalengka, 2023)
The aim of this study is to investigate the socio and cultural effects of football among the Students of the Physical Education Department at Kandahar University The foot obviously has a lot of symbolic significance. Because football is primarily played with the foot, it has issues with identity, class, and history. Due to its connection to the